EVALUATION OF THE CLINICAL SUCCESS OF 56 AUTOTRANSPLANTED TEETH - A RETROSPECTIVE STUDY - M Starosta; M Bartoš; R Foltán (Czech Dental Chamber, 2024)
Introduction, aim: At present, tooth autotransplantation is considered one of the therapeutic methods for the replacement of lost teeth. In the last 30 years, the method of tooth autotransplantation has been developed and refined and has become a basic knowledge of dental practitioners. The aim of this clinical retrospective study was to examine children and adult patients with tooth autotransplantation and obtain survival and success rates. Another aim was to determine other specifics of autotransplantation in each group with conclusions relevant for clinical practice. Methods: The study population consisted of the patients referred consecutively for tooth autotransplantation to a specialist department between years 2016 and 2021. The specialization of the referring dentist, the suitability and feasibility of the transplantation, and the donor and recipient area of the tooth graft were recorded. In 2022, clinical and radiological evaluation of the autotransplanted teeth was performed. Patients were divided into two groups according to age in time of autotransplantation, namely under 18 years and over 18 years. Results: Overall, 73 patients in the age range of 10-59 years were referred for autotransplantation. The mean age was 21.43 years with a median age of 17 years. Autotransplantation was not recommended in 12 patients. A total of 68 autotransplantations were performed, but at the time of examination, 12 did not meet the minimum 6-month follow up, so they were excluded from the evaluation. A total of 56 autotransplants were evaluated. In the group of children, there were 27 patients aged 10-17 years who underwent autotransplantation of at least one permanent tooth. A total of 34 teeth were transplanted. The evaluation of the transplanted teeth was performed 6-50 months after the transplantation with a mean follow-up time of 24 months. The survival rate was 100% and the success rate was 91%. The adult group consisted of 22 patients aged 18-59 years and a total of 22 teeth were transplanted. The evaluation of the transplanted teeth was performed 6-72 months after transplantation with a mean of 33 months. The survival rate was 95%, the success rate 77%. Conclusion: The use of autograft to replace undeveloped or lost teeth was most often indicated by orthodontists. In the patients under 18 years of age, the premolars are the predominant donor area and recipient area. In patients over 18 years of age, the third molars are the predominant donor area and the mandibular molars the predominant recipient area. Both age groups have high survival and success rates of autograft and this procedure can be considered as a predictable method of tooth replacement.